2013
DOI: 10.1038/pr.2013.48
|View full text |Cite
|
Sign up to set email alerts
|

Establishing lung gas volumes at birth: interaction between positive end-expiratory pressures and tidal volumes in preterm rabbits

Abstract: Background:We investigated the effects of positive endexpiratory pressure (PEEP) and tidal volume (V T ) on lung aeration, pulmonary mechanics, and the distribution of ventilation immediately after birth using a preterm rabbit model. Methods: Sixty preterm rabbits (27 d) received volumetargeted positive pressure ventilation from birth, with one of the 12 combinations of PEEP (0, 5, 8, or 10 cmH 2 O) and V T (4, 8, or 12 ml/kg). Outcomes included functional residual capacity (FRC), peak inflating pressure (PIP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
(55 reference statements)
0
17
0
Order By: Relevance
“…A SI of 10 s or greater was needed to develop FRC in neonatal rabbits (41). Physiologically, a 30-s SI improved circulatory return in asphyxiated near-term lambs, whereas a series of five 3-s SI (as suggested by the European resuscitation guidelines) did not increase heart rate over ventilation alone (21,30).…”
Section: Discussionmentioning
confidence: 99%
“…A SI of 10 s or greater was needed to develop FRC in neonatal rabbits (41). Physiologically, a 30-s SI improved circulatory return in asphyxiated near-term lambs, whereas a series of five 3-s SI (as suggested by the European resuscitation guidelines) did not increase heart rate over ventilation alone (21,30).…”
Section: Discussionmentioning
confidence: 99%
“…PEEP is essential in the preterm lung (5,14). In our study, we used a PEEP (8 cmH 2 O) previously shown to be appropriate in preterm lambs (6,11,16,17), and higher than that used in similar animal studies (5,9,10,14,15,20,29), suggesting our results are due to differences in recruitment strategy and not subsequent ventilator management.…”
Section: Discussionmentioning
confidence: 86%
“…In our study using intubated preterm lambs, we systematically describe the interrelationship between the use of antenatal corticosteroids, exogenous surfactant therapy, and two distinct recruitment strategies applied Unlike previous animal studies of respiratory care at birth (6,(10)(11)(12)15,16,(20)(21)(22)(27)(28)(29)(30), our study involved a large sample size. Pooling all epochs, the use of an OLV stepwise PEEP approach significantly improved C dyn and oxygenation compared to a 30-s 40 cmH 2 O SI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations